PENGEMBANGAN BIG BOOK BERBASIS KEARIFAN LOKAL UNTUK PEMBELAJARAN MEMBACA PERMULAAN DI SD - Iyut Muzdalifah; Heru Subrata (Universitas Negeri Surabaya, 2022)
This study aims to describe the effectiveness of developing big book media based on local wisdom on early reading learning in first grade elementary school students. This study uses a literature review method that focuses on the use of literature in similar research journals using a Research and Development (R&D) approach. Based on the literature review, the results obtained in the form of the conclusion that any research using the big book media shows the effectiveness of the media when used in early reading learning for students in lower grades. Bigbook media makes learning closer to students, fun and meaningful. This media is in accordance with the characteristics and needs of first grade elementary school students and improves reading skills in students as evidenced by the positive response in student learning outcomes in understanding information